Analisis Distribusi Spasial dan Keterlayanan Fasilitas Bank Sampah di Kota Tanjungpinang - Zuleriwati A.S; Nefriwati Hilmi; Aditia Ayu Rahma Nabila; Meylia Vivi Putri; Halimah Fahri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the spatial distribution of waste banks in Tanjungpinang City and to identify gap areas or residential zones that remain underserved by these facilities. A quantitative descriptive approach was employed, utilizing spatial analysis based on Geographic Information Systems (GIS). The dataset consisted of waste bank coordinate points, administrative boundaries, residential zoning maps, and population density data. Analytical procedures included buffer analysis to assess service coverage within a 300–500 meter radius, overlay analysis to identify serviced and unserviced residential areas, and a gap area assessment to quantify disparities across sub-districts. The findings indicate that the spatial distribution of waste banks in Tanjungpinang is uneven, with the highest concentration located in Bukit Bestari (25 units) and Tanjungpinang Timur (24 units), while Tanjungpinang Barat and Tanjungpinang Kota have significantly fewer facilities. Buffer analysis revealed that Bukit Bestari achieved the highest service coverage at 70.17%, followed by Tanjungpinang Kota (52.54%), Tanjungpinang Barat (49.07%), and Tanjungpinang Timur (46.47%). Overall, only 52.99% of the total 7.68 km² of residential areas are currently served by waste bank facilities. These results highlight spatial inequalities in access to waste management services, particularly in peripheral and densely populated neighborhoods. The study concludes that strategic expansion and equitable redistribution of waste bank facilities are necessary to promote more effective, inclusive, and sustainable waste management practices in Tanjungpinang City